Français écrit — français parlé — français prononcé: la quête du mot dans la poésie cubiste de Max Jacob - Kotowska, Katarzyna (Verbum – Analecta Neolatina, 2005)
In his cubist poetry, Max Jacob follows the declaration of Mallarmé to create poems not with ideas but with words. He was advocating the siginifiant to the detriment of signifié. Thus, for Jacob, a word has become the same thing as the object for painters - an element of the construction. The ordinary and everyday objects enchanted cubist aesthetics. The same process can be observed in Jacob's poetry. The poet considers everyday spoken French as equivalent to the objects in cubist pictures. The discrepancy between spoken and written French has also been shown to be able to bring closer cubist poetry to painting. Among others things, he uses multiple-word games which have the purpose of highlighting the essence of words, just like in cubist pictures where an object suffers all kind of decompositions, syntheses and analyses.